The Efficacy of Fecal Microbiota Transplantation for Children With Tourette Syndrome: A Preliminary Study - Zhao, Hui-Jun; Luo, Xi; Shi, Yi-Chao; Li, Jian-Feng; Pan, Fei; Ren, Rong-Rong; Peng, Li-Hua; Shi, Xiu-Yu; Yang, Guang; Wang, Jing; Hu, Lin-Yan; Zou, Li-Ping; et al. (Frontiers in Psychiatry, 2020)
Therapies for Tourette syndrome (TS) are insufficient, and novel therapies are needed. Fecal microbiota transplantation (FMT) has been a potential therapy for several neurological diseases. Here, we report a preliminary study to investigate the effects of FMT on patients with TS. Five patients with TS received a single administration of FMT via endoscopy. Tic symptoms were assessed by Yale Global Tic Severity Scale-Total Tic Score (YGTSS-TTS) and adverse effects were recorded at week 8 following FMT. Lipopolysaccharide (LPS) levels and 14 cytokines levels were measured. The microbiota profile in faeces were analysed by shotgun metagenomics. Four patients (4/5) responded positively to FMT (YGTSS-TTS reduction rate >25%) at week 8 without severe adverse effects. The levels of LPS and cytokines varied after FMT. FMT shifted the composition of the gut microbiota in patients close to that of the donor and continuously changed the abundance of Bacteroides coprocola, Dialister succinatiphilus and Bacteroides vulgatus. The restoration of B.coprocola was correlated with the improvement in tic symptoms (Spearman R= -0.900, P= 0.037). In conclusion, FMT was indicated a potential effective and safe alternative for patients with TS. However, larger clinical trials are needed to confirm the influence of microbiota in TS. Trial registration chictr.org.cn Identifier: ChiCTR-IIR-17011871, URL: http://www.chictr.org.cn/showproj.aspx?proj=19941